2021
DOI: 10.1007/s11934-021-01065-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ureteroscopy in Treatment of Upper Tract Urothelial Carcinoma

Abstract: Purpose of Review Upper tract urothelial carcinoma (UTUC) is uncommon accounting for less than 10% of all urothelial tumours. Ureteroscopic management (URS) is the first line treatment for low-risk disease and has been increasingly utilised due to technological advances and increasing surgical experience. This review looks at patient outcomes relating to URS, emerging technologies and the role of adjuvant intracavitary therapy in the management of UTUC. Recent Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Ng Chieng et al reported a high local recurrence rate of 46% at a mean follow-up time of 4.9 months after endoscopic treatment. 10 The risk of intravesical recurrence after treatment of UTUC is relatively high (30-40%), whereas the recurrence rate in the contralateral upper urinary tract, as observed in our two cases, is rare (2-6%). 11 Moreover, there are still some issues to be discussed.…”
Section: Discussionmentioning
confidence: 46%
“…Ng Chieng et al reported a high local recurrence rate of 46% at a mean follow-up time of 4.9 months after endoscopic treatment. 10 The risk of intravesical recurrence after treatment of UTUC is relatively high (30-40%), whereas the recurrence rate in the contralateral upper urinary tract, as observed in our two cases, is rare (2-6%). 11 Moreover, there are still some issues to be discussed.…”
Section: Discussionmentioning
confidence: 46%
“…This needs to be prospectively evaluated in larger randomized studies. 23,24 The present study had a few limitations. Firstly, there are inevitable biases due to its retrospective design, and patients receiving non-protocol-based URS biopsy procedures including variations in the quality of tissue samples obtained.…”
Section: Discussionmentioning
confidence: 89%
“…Upper tract urothelial carcinoma (UTUC) accounts for up to 10% of all urothelial neoplasms [1]. On the basis of the current European Association of Urology (EAU) guidelines, UTUCs can be divided into two groups for clinical decision making: low-risk and high-risk [2].…”
Section: Introductionmentioning
confidence: 99%